The Legitimacy of the Antarctic Treaty System - Scherzer, Joern (University of Canterbury, 2005)
Recognising that the Antarctic is part of the global commons that, depending on one's per- spective, belongs to either nobody or everybody, this paper reviews and critically examines the literature with regard to the variety Of perspectives about the legitimacy Of the Antarctic Treaty System (ATS) as the international legal regime' for governing and managing the Antarctic. The ATS refeß to a whole complex of arrangements made for the purpose Of regulating relations among states in the Antarctic. According to Art.l(e) of the Protocol (1991), the Antarctic Treaty System means: "the Antarctic Treaty, the measures in effect under that Treaty, its associated separate international instruments in force and the measures in effect under those instruments*'. The ATS is thus, according to (Stokke & Vidas, 1996, pp.42-43), composed of four major components: the Antarctic Treaty as it constitutes the basis for all other parts of the ATS, those recommendations adopted at Consultative Meetings that are in effect, treaties in force that have been adopted on the basis of the Antarctic Treaty, i.e. the 1972 Convention for the Conservation of Antarctic Seals, the 1980 Convention on the Con- servation Of Antarctic Marine Living Resources and the 1991 Protocol on Environmental Protection and its annexes , as well as measures in effect under those treaties. The main finding here is that at present the ATS can neither be considered legitimate nor illegitimate. However, it may be regatded as a relatively legitimate system Of governance for the Antarctic and the legitimacy of the system has, according to a number of authors, increased considerably since its emergence. The paper will begin by outlining the pmblematic nature of legitimacy as a Concept in an international context and draws attention to relevant literature directly concerned with the Recognising that the Antarctic is part of the global commons that, depending on one's per- spective, belongs to either nobody or everybody, this paper reviews and critically examines the ...